Identifying Students’ Incorrect Common-Sense Knowledge in Forces and Motion: Recommendations for Developing Computer-Based Learning Media - Adha, Ahmad Ridlotul; Sutopo, Sutopo; Nasikhudin, Nasikhudin (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2023)
Conceptual understanding is a crucial area in physics education research, focusing on students’ comprehension of fundamental principles. Force and motion, integral topics within this field, are inherently linked to students’ daily experiences. Numerous studies have identified the persistence of common sense knowledge among students. This research presents a literature review aimed at identifying such consistently held misconceptions. We analyzed 17 papers sourced from Publish or Perish 8, Google Scholar, and Scopus. Our analysis revealed that the concepts of impetus and active force are the most persistent forms of common sense knowledge, influenced by real-life experiences. Additionally, students’ difficulties with kinematics tend to diminish over time. With advancements in technology and educational methodologies, it is anticipated that these incorrect common sense understandings can be progressively reduced and eventually eliminated.DOI: https://doi.org/10.17977/jps.v11i42023p123